Regulation of Granulocyte Colony-Stimulating Factor and Its Receptor in Skeletal Muscle is Dependent Upon the Type of Inflammatory Stimulus. - Wright, Craig Robert; Brown, Erin Louise; Della Gatta, Paul A; Fatouros, Ioannis G; Karagounis, Leonidas G; Terzis, Gerasimos; Mastorakos, Georgios; Michailidis, Yannis; Mandalidis, Dimitris; Spengos, Kontantinos; Chatzinikolaou, Athanasios; Methenitis, Spiros; et al. (J Interferon Cytokine Res, 2015)
The cytokine granulocyte colony-stimulating factor (G-CSF) binds to its receptor (G-CSFR) to stimulate hematopoietic stem cell mobilization, myelopoiesis, and the production and activation of neutrophils. In response to exercise-induced muscle damage, G-CSF is increased in circulation and G-CSFR has recently been identified in skeletal muscle cells. While G-CSF/G-CSFR activation mediates pro- and anti-inflammatory responses, our understanding of the role and regulation in the muscle is limited. The aim of this study was to investigate, in vitro and in vivo, the role and regulation of G-CSF and G-CSFR in skeletal muscle under conditions of muscle inflammation and damage. First, C2C12 myotubes were treated with lipopolysaccharide (LPS) with and without G-CSF to determine if G-CSF modulates the inflammatory response. Second, the regulation of G-CSF and its receptor was measured following eccentric exercise-induced muscle damage and the expression levels we investigated for redox sensitivity by administering the antioxidant N-acetylcysteine (NAC). LPS stimulation of C2C12 myotubes resulted in increases in G-CSF, interleukin (IL)-6, monocyte chemoattractant protein-1 (MCP-1), and tumor necrosis factor-α (TNFα) messenger RNA (mRNA) and an increase in G-CSF, IL-6, and MCP-1 release from C2C12 myotubes. The addition of G-CSF following LPS stimulation of C2C12 myotubes increased IL-6 mRNA and cytokine release into the media, however it did not affect MCP-1 or TNFα. Following eccentric exercise-induced muscle damage in humans, G-CSF levels were either marginally increased in circulation or remain unaltered in skeletal muscle. Similarly, G-CSFR levels remained unchanged in response to damaging exercise and G-CSF/G-CSFR did not change in response to NAC. Collectively, these findings suggest that G-CSF may cooperate with IL-6 and potentially promote muscle regeneration in vitro, whereas in vivo aseptic inflammation induced by exercise did not change G-CSF and G-CSFR responses. These observations suggest that different models of inflammation produce a different G-CSF response.
Keywords: Acetylcysteine; Adult; Antioxidants; Chemokine CCL2; Exercise; Granulocyte colony-stimulating factor; Humans; Inflammation; Interleukin-6; Lipopolysaccharides; Male; Muscle, Skeletal; Myoblasts; Neutrophils; Receptors, Granulocyte Colony-Stimulating Factor; RNA, Messenger; Tumor Necrosis Factor-alpha; Young Adult